2015
DOI: 10.1039/c4md00526k
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-interacting properties of the functionalised fatty acid moiety of muraymycin antibiotics

Abstract: A simplified model system is introduced to elucidate the significance of the ω-functionalised fatty acid moiety of muraymycin nucleoside antibiotics for membrane interaction and penetration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…We have reported a model system to study the membrane-interacting properties of the ω-functionalized fatty acid moiety of A-series muraymycins such as 3 , indicating both an efficient membrane accumulation and penetration mediated by the guanidinium-containing structural motif. [13] This present study encourages further investigations on the membrane-penetrating properties of O -acylated muraymycins of the A- and B-groups.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We have reported a model system to study the membrane-interacting properties of the ω-functionalized fatty acid moiety of A-series muraymycins such as 3 , indicating both an efficient membrane accumulation and penetration mediated by the guanidinium-containing structural motif. [13] This present study encourages further investigations on the membrane-penetrating properties of O -acylated muraymycins of the A- and B-groups.…”
supporting
confidence: 62%
“…This finding supports a previous hypothesis that the fatty acyl unit might instead contribute primarily to the cellular uptake rather than target interaction. [10d,13] On the other hand, muraymycin D1 7 was a ca. 30-fold less active MraY inhibitor than C1 6 , although it only differs in the missing β-hydroxy group in the leucine moiety.…”
mentioning
confidence: 99%
“…Ries et al have further shown that the -guanylated fatty acid substituent found in the most active muraymycins is important for localisation of the antibiotic into the cytoplasmic membrane of the target organism [26].…”
Section: Nucleoside Natural Product Inhibitors Of Mray and Related Enmentioning
confidence: 99%
“…Consequently, the need emerged to find suitable methods to evaluate and predict the permeability of antiinfectives. These attempts include in vitro approaches such as liposome [14] or outermembrane-vesicle swelling assays [15], electrophysiological studies [16][17][18], as well as assays employing lipid-coated filters [19,20], reconstituted bacterial vesicles [21] or giant unilamellar vesicles (GUV's) [22]. Further, important assays have been developed using living bacteria [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%